Characterization of Type I and IV Collagens by Raman Microspectroscopy: Identification of Spectral Markers of the Dermo-Epidermal Junction. Issue 5 (11th July 2012) - Nguyen Nguyen, T. T. T. T.; Gobinet Gobinet, C. C.; Feru Feru, J. J.; -Pasco -Pasco, S. Brassart S. Brassart; Manfait Manfait, M. M.; Piot Piot, O. O.
Abstract : Type I and IV collagens are important constituents of the skin. Type I collagen is found in all dermal layers in high proportion, while type IV collagen is localized in the basement membrane of the dermo-epidermal junction (DEJ). These proteins are strongly altered during aging or cancer progression. Although they possess amino acid compositions which, are close, they present also important structural differences inducing specific physicochemical properties. Raman spectroscopy is based on a nondestructive interaction of the light with the matter. This technique permits to probe the intrinsic molecular composition of the samples without staining or particular preparation. The aim of our research is to study the correlation between the molecular conformations of type I and IV collagens and their Raman features. We showed that signals specific of each protein can be revealed and that they translate structural differences between the two collagens. From this collagens spectral characterization, the analysis of skin sections also permitted to identify spectral markers of dermis, epidermis, and epidermis/dermis interface. These preliminary results represent basic data for further studies, particularly to probe skin molecular alterations induced by chronologic aging.